RANCANG BANGUN WEBSITE E-LEARNING SMAN 1 PALANGKA RAYA - Widiatry Widiatry; Agra Nugraha (Universitas Palangka Raya, 2018)
A variety of new concepts and techniques in teaching has been widely developed to replacetraditional methods that rely solely on a one-way teaching method in the class. One of theteaching methods that are being developed in SMAN 1 Palangka Raya is currently the e-learning,where teachers can help in distributing their materials without having to be in class by using theinternet. In e-learning this implement search algorithms namely the Boyer-Moore algorithmwhich is expected to be able to support the system to be able to correct the answers through hisessay, do a word search of the position of the right to the left position. This algorithm has aprinciple of good suffix (a character who sought similar characters aligned with) as well as theprinciple of bad character (characters that are not selected will be similar). Website developmente-learning uses the method Waterfall. To design this application used the method of structuraldesign i.e. making Entity Relationship (ER) and making Data Flow diagrams (DFD) fordesigning and documenting software systems based on the flow of data. In making this softwareusing PHP as a scripting language used to create Web page and MySQL database as a datastorage. Testing is done using Blackbox testing methods.